2015
DOI: 10.1007/s00259-015-3273-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between left ventricular diastolic function and myocardial sympathetic denervation measured by 123I-meta-iodobenzylguanidine imaging in Anderson-Fabry disease

Abstract: The present findings provide the first demonstration of a cardiac sympathetic derangement in AFD patients with preserved LV ejection fraction, which is mostly related to LV diastolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…ese pathological changes, associated with GL-3 related damage to the sympathetic nervous system, cause the onset of cardiac conduction disorders, left ventricular hypertrophy, and heart failure even with preserved ejection fraction [45,46].…”
Section: Anderson-fabry Disease and Endothelial Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…ese pathological changes, associated with GL-3 related damage to the sympathetic nervous system, cause the onset of cardiac conduction disorders, left ventricular hypertrophy, and heart failure even with preserved ejection fraction [45,46].…”
Section: Anderson-fabry Disease and Endothelial Dysfunctionmentioning
confidence: 99%
“…In parallel to a drastic reduction in plasma, urine, and tissue concentrations of GL-3, ERT was found to determine a variety of clinical effects: from slowing the decline in estimated glomerular filtration rate (eGFR), to reducing or stabilizing cardiac remodelling and ameliorating neurological and gastrointestinal symptoms [42,48]. e lack of clinical improvements, but also of further deterioration, during ERT was regarded as a marker of clinical benefit in an otherwise progressive, debilitating disease associated with a risk of premature mortality [42,45,46,48,51,52].…”
Section: Enzyme Replacement Therapy and Emergingmentioning
confidence: 99%
“…Spinelli et al reported a reduced H/M ratio in AFD patients, but did not show localization of the reduced MIBG uptake. 4 A possible explanation for this observation is regional differences in cardiac innervation. The inferior wall, as compared with the anteroseptal wall, is predominantly innervated by parasympathetic nerves and less innervated by sympathetic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant autonomic nervous system responses cause sympathetic hyperactivity and reduced parasympathetic activity. 10,11 Besides, impaired cardiac innervation is related to ventricular dysfunction. 12 It has been shown that hyperactivation of the sympathetic fibers provide inotropic support to the failing heart and peripheral vasoconstriction to maintain arterial pressure.…”
Section: Discussionmentioning
confidence: 99%